ChemInform Abstract: Catalytic sp3 C—H Oxidation of Peptides and Their Analogues by Radical Cation Salts: From Glycine Amides to Quinolines. Issue 10 (11th March 2014) - Jia, Xiaodong; Wang, Yaxin; Peng, Fangfang; Huo, Congde; Yu, Liangliang; Liu, Jing; Wang, Xicun
Abstract A catalytic α‐sp3 C—H oxidation of glycine amides and peptides is achieved under radical cation salt catalysis in the presence of oxygen, producing a series of substituted quinolines.